2009
DOI: 10.1111/j.1469-7580.2009.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of end‐to‐end and end‐to‐side nerve repair (neurorrhaphy) in the rat brachial plexus

Abstract: Proximal nerve injury often requires nerve transfer to restore function. Here we evaluated the efficacy of endto-end and end-to-side neurorrhaphy of rat musculocutaneous nerve, the recipient, to ulnar nerve, the donor. The donor was transected for end-to-end, while an epineurial window was exposed for end-to-side neurorrhaphy. Retrograde tracing showed that 70% donor motor and sensory neurons grew into the recipient 3 months following end-to-end neurorrhaphy compared to 40-50% at 6 months following end-to-side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 34 publications
4
52
0
1
Order By: Relevance
“…The most important result was that all three methods retained the nerve and muscle function without difference in quality and time recovery. Unlike these findings, Liao et al 18 and Jaeger et al 22 found superior results regarding the time and quality of recovery for the group with end-to-end neurorrhaphy. However, we could observe that the the research conducted comparing the end-to-end and end-to-side neurorrhaphy used different donor nerves, which causes an important bias in the research and makes it difficult to compare with our findings, since we were careful to marter the same nerve as a donor in all techniques 18,19,22 .…”
Section: ■ Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The most important result was that all three methods retained the nerve and muscle function without difference in quality and time recovery. Unlike these findings, Liao et al 18 and Jaeger et al 22 found superior results regarding the time and quality of recovery for the group with end-to-end neurorrhaphy. However, we could observe that the the research conducted comparing the end-to-end and end-to-side neurorrhaphy used different donor nerves, which causes an important bias in the research and makes it difficult to compare with our findings, since we were careful to marter the same nerve as a donor in all techniques 18,19,22 .…”
Section: ■ Discussionmentioning
confidence: 85%
“…However, many authors doubted wether this nerve repair could substitute completely the traditional end-to-end neurorrhaphy and keep saying that this is the best method to use in nerve repair 18,19,22 . The present study compared the efficiency of three different techniques of neurrorhaphy: the end-to-end, end-to-side and side-to-end.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations